2019
DOI: 10.1186/s42826-019-0034-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronic oral administration of Passiflora incarnata extract has no abnormal effects on metabolic and behavioral parameters in mice, except to induce sleep

Abstract: Although the number of prescriptions and dependence on sleeping pills are increasing, the associations with unexpected abnormal behaviors and metabolic diseases caused by the overuse of sleeping pills are not well understood. In particular, such as abnormal eating-behavior and the occurrence of metabolic disorders caused by psychological unstable states are reported. For this reason, herbal medicine, which has not had such side effects in recent years, is attracting attention as an alternative medicine/food fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
1
0
3
Order By: Relevance
“… 32 A 2019 animal study concluded that Passionflower revealed no adverse effects in mice through chronic use of the herb. 33 Despite the lack of adverse effects reported in these limited studies there are still a few cautions to consider. Passionflower does contain the flavonoid 5,7-dihydroxyflavone, 34 more commonly called chrysin which has been shown to inhibit the enzyme aromatase, affecting the conversion of testosterone to estradiol, 35 and prolonged use should be contraindicated in individuals with hormone-balance conditions such as Polycystic Ovary Syndrome (PCOS).…”
Section: The Science and Safety Of Common Botanicals For Stressmentioning
confidence: 99%
“… 32 A 2019 animal study concluded that Passionflower revealed no adverse effects in mice through chronic use of the herb. 33 Despite the lack of adverse effects reported in these limited studies there are still a few cautions to consider. Passionflower does contain the flavonoid 5,7-dihydroxyflavone, 34 more commonly called chrysin which has been shown to inhibit the enzyme aromatase, affecting the conversion of testosterone to estradiol, 35 and prolonged use should be contraindicated in individuals with hormone-balance conditions such as Polycystic Ovary Syndrome (PCOS).…”
Section: The Science and Safety Of Common Botanicals For Stressmentioning
confidence: 99%
“…principais resultados e conclusões dos estudos. As metodologias utilizadas para avaliação das propriedades calmantes das plantas nos estudos pré-clínicos em modelos experimentais com roedores incluíram principalmente a avaliação de comportamentos ansiosos, de interação social e da atividade motora espontânea 14 , testes do labirinto em cruz elevado e teste do nado forçado 15,16 , teste de campo aberto 17 , tempo para adormecer e duração de sono induzido 18,19 , além de mensuração de níveis sanguíneos de melatonina 19,20 . Nos modelos utilizando peixes-zebra, a atividade ansiolítica foi avaliada através de parâmetros relacionados à mobilidade dos animais durante períodos claros versus escuros antes e depois de serem submetidos aos derivados das plantas estudadas [21][22][23] .…”
Section: Extração Dos Dadosunclassified
“…No estudo de Aman et al 17 , a atividade ansiolítica e sedativa do maracujá se mostrou similar à do Diazepam. O tratamento dos animais com extrato de P. incarnata também provocou aumento do fator neurotrófico derivado do cérebro 54 , dos níveis sanguíneos de melatonina 19,20 e melhora da memória 53,54 .…”
Section: Passiflora Incarnata -Maracujáunclassified
See 1 more Smart Citation